IMPLEMENTATION OF COMMUNITY-BASED DRINKING WATER PROVISION AND SANITATION PROGRAM (PAMSIMAS) - Elanda Wulandari; Dimas Imaniar; Safrieta Jatu Permatasari (Riviera Publishing, 2024)
This research was motivated by problems that stemmed from the non-implementation of the Pamsimas program in Bomo Village, Blimbingsari District, Banyuwangi Regency even though a building had been provided, as well as the presence of damaged or incomplete equipment in the Pamsimas building so that the implementation of the program was hampered. This research aims to evaluate the effectiveness of village development programs in Blimbingsari District, especially through community-based drinking water and sanitation programs, with a focus on changes in Bomo Village. This research uses a qualitative descriptive research type. The data collection techniques were interviews and observations based on Pamsimas program data in Bomo Village. The results of research conducted using several indicators proposed by George Edward III (1980), namely communication, resources, disposition and bureaucratic structure, show that implementation, communication is very important and plays an important role in knowing what the implementer must do. Disposition as an implementing attitude. The important thing about disposition variables is; bureaucratic appointments, and incentives. If the Bomo Village Government wants to get effective results, its officials must not only know but also have the ability to implement it. There are 2 main characteristics of a bureaucratic structure, namely; standard operating procedures, and fragmentation. Bureaucratic structure can influence the successful implementation of a policy. Policy implementation is a quite complex process that requires strong and conductive bureaucratic cooperation. The community-based drinking water and sanitation program (pamsimas) in Bomo village, Blimbingsari subdistrict, Banyuwangi district has not been running well and the implementation process is still not optimal because the community still complains about the pamsimas program system.